THE ANALYSIS OF EMILY DICKINSON’S LIFE BACKGROUND ON THE INTROVERT AND EXTROVERT FOUND IN HER POEM ENTITLED “BECAUSE I COULD NOT STOP FOR DEATH" - Edi Firman; Tawali Tawali (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
This research was aimed to revealed the analysis of Emily Dickinson’s life background on the introvert and extrovert found in her poem entitled “Because I Could Stop for Death”. The method on this research was qualitative descriptive. The techniques of data collection used documentation, close reading, identification, classification, and note taking. The techniques of data analysis used the interactive model namely data reduction, data display, and conclusion drawing or verification. The analysis of “Because I Could Not Stop for Death” by Emily Dickinson’s used theory personality of Jung G Carly, especially concerning in Introvert and Extrovert. The poem contains six stanzas. In every stanza there are four lines. The conclusion of this research was the total of Introvert were found 5 and total of Extrovert found1. In other words the general problem of this study had been answered.